The impact of parental behaviors on children's negative emotions - Tong, Sijia (2015)
The study examined the role of different parental behaviors on children’s negative emotions. Parents of 152 Finnish first grade children (79 girls and 73 boys) filled in diary-formed questionnaires which measure parental behaviors including affection, behavioral control and psychological control. Children’s negative emotions are also measured by diary-formed questionnaires which are filled in by their parents. The results showed that parental affection was negatively related to children’s negative emotions while parental psychological control was positively related to children’s negative emotions. The study did not find relation between parental behavioral control and children’s negative emotions.